Penerapan Peplum Pada Cheongsam Dress - Suryani, Retno Fajar; Nahari, Inty (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2025)
The purpose of this study was to determine the process of making peplum on Cheongsam Dress and find out the results of making peplum on Cheongsam Dress. The method used in this study is the creation of works consisting of four stages namely; pre-design stage, design stage, realization stage and presentation stage. The results of this study are: The process of making peplum on Cheongsam Dress starts from making patterns and then cutting materials, sewing process, to the finished result of applying peplum on Cheongsam Dress. The selection of material characteristics using thick and shiny duces with a light brown color makes the peplum on the Cheongsam Dress look elegant, and there is a phoenix brocade accent for decoration on the Cheongsam Dress.